Nonlinearity of the combined warm ENSO and QBO effects on the Northern Hemisphere polar vortex in MAECHAM5 simulations - Calvo Fernández, Natalia; Giorgetta, Marco A.; García Herrera, Ricardo Francisco; Manzini, Elisa (Journal of Geophysical Research: Atmospheres, 2009)
The influence of the quasi-biennial oscillation (QBO) on the Northern Hemisphere (NH) polar vortex response to warm El Nino-Southern Oscillation (ENSO) events and the impact of the warm ENSO events on the QBO signal in the NH polar stratosphere have been analyzed using the Middle Atmosphere ECHAM5 model. The experiment setup was designed to include simulations of extended NH winter seasons for either strong easterly or strong westerly phases of the tropical QBO, forced with either sea surface temperatures (SSTs) from the strong ENSO event that occurred in 1997/1998 or with climatological SSTs. It has been found that the weakening and warming of the polar vortex associated with a warm ENSO are intensified at the end of the winter during both QBO phases. In addition, the westerly QBO phase delays the onset of the warm ENSO signal, while the easterly QBO phase advances it. Warm ENSO events also impact the extratropical signal of the QBO by intensifying ( weakening) the QBO effects in early ( late) winter. Therefore, it appears that during warm ENSO events the duration of QBO signal in the northern extratropics is shortened while its downward propagation accelerated. Our dynamical analysis has revealed that these results are due to changes in the background flow caused by the QBO combined with changes in the anomalous propagation and dissipation of extratropical waves generated by warm ENSO. In both cases, a nonlinear behavior in the response of the polar vortex is observed when both warm ENSO and the easterly phase of the QBO operate together. These results suggest that the Arctic polar vortex response to combined forcing factors, in our case warm ENSO and the QBO phenomena, is expected to be nonlinear also for other coexistent forcing factors able to affect the variability of the vortex in the stratosphere. Max Planck Institute for Meteorology (Alemania) Ministerio de Ciencia, Innovación y Universidades (España) Programa Fulbright Comisión de España Depto. de Física de la Tierra y Astrofísica Fac. de ...